(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
The article analyzes the scientific basis for improving silkworm productivity. Achieving high productivity begins with the cleanliness of the silkworm rearing room, where the amount of moisture, temperature, and nutrition play a key role. The embryonic development of eggs is primarily determined by the temperature and relative humidity of the air in the incubator.